(untitled) (Nativa, 2022)
Plantios de árvores proporcionam aumento dos estoques de carbono do solo, mas estudos envolvendo espécies nativas da Amazônia são incipientes. Objetivou-se avaliar a variação espacial dos atributos físicos e estoque de carbono orgânico no solo em plantio de paricá. Na área de estudo, coletaram-se amostras de solo nas profundidades de 0 a 20 cm e de 20 a 40 cm e os parâmetros analisados foram: textura do solo, macroporosidade, microporosidade, densidade aparente do solo, resistência mecânica do solo à penetração, teores e os estoques de carbono orgânico do solo. Interpolou-se os dados pelo inverso do quadrado da distância. A variação espacial dos atributos físicos do solo no plantio foi influenciada pela textura. Houve baixa amplitude da variação espacial dos teores e estoques de carbono orgânico do solo. O plantio de paricá apresentou eficiência na fixação de carbono no solo em profundidade. Palavras-chave: silvicultura; sequestro de carbono; física do solo; mudança climática. Spatial variation of physical attributes and soil carbon stocks in a Schizolobium amazonicum plantation in the amazon ABSTRACT: Tree plantations provide an increase in soil carbon stocks, but studies involving native Amazonian species are incipient. The objective was to evaluate the spatial variation of physical attributes and soil organic carbon stock in a paricá plantation. In the study area, soil samples were collected at depths of 0 to 20 cm and 20 to 40 cm and the parameters analyzed were: soil texture, macroporosity, microporosity, soil bulk density, mechanical soil resistance to penetration, and soil organic carbon content and stocks. The data were interpolated by the inverse of the square of the distance. The spatial variation of soil physical attributes at planting was influenced by texture. There was a low range of spatial variation in soil organic carbon content and stocks. Paricá planting was efficient in fixing soil carbon at depth. Keywords: silviculture; carbon sequestration; soil physics; climate change.